Resistance to Forced Labour in Colonial Nigeria (2017)
Until the enactment of the Forced Labour Ordinance of 1933, the employment of forced or compulsory labour for sanitary measures, maintenance of roads, clearing of markets, public works and personal services of chiefs persisted in Nigeria through the manipulation of native' laws and customs by the colonial state. This paper argues that discontent with forced labour brought into play new power relations between the colonial state and the colonial subjects. In defiance of the international convention, forced labour was not regulated by any statute in Nigeria. It was discussed in loose and general terms without any serious attempt to ascertain where and how it persisted. Many native authorities resorted to forced labour in order to balance their budgets but their decreasing power over young men made it difficult over the years. From the 1940s, some able-bodied men refused to perform forced labour, arguing that having paid taxes; they could not be called upon for a communal service or political labour. There were petitions against forced labour. This paper explores the role of Christian missionaries and nationalists in the struggle against forced labour.